Fingerprint-inspired dual-mode pressure sensor for robotic static and dynamic perception. (1st December 2022) - Fu, Xiang; Dong, Jianing; Li, Ling; Zhang, Liang; Zhang, Jiqiang; Yu, Longteng; Lin, Qinhao; Zhang, Jiahe; Jiang, Chengpeng; Zhang, Jin; Wang, Yancheng; Wu, Wenzhuo; et al.
Abstract: The capability of perceiving the uncertain environment and the adaptation to external stimuli is of main concern in robotics. Inspired by the outer microstructure of the human fingerprint, a dual-mode tactile sensor is developed, consisting of capacitive sensing units for the static force perception, hybrid nanogenerators for the dynamic response and fingerprint-like hierarchical winkles. By leveraging the individual areas and jointing spaces, eight functional electrode points are defined, achieving position sensing with clear differentiation even under various operations, including tapping and sliding interactions. After conformally interrelating the piezoelectric layer into the triboelectric separator, the carbon-silicone composites enhanced capacitor with the as-designed functions can convert external mechanical energy into electricity, whilst detecting three-axis force with high sensitivity and wide linear range. Moreover, the device is demonstrated to detect high-frequency vibration and slow micro-friction phenomena, ensuring a stable and repeatable identification of the typical robotic hand movement. Graphical Abstract: ga1 Highlights: Inspired by the microstructure of the human fingerprint, a dual-mode tactile sensor is developed. The sensor can decouple three-axis force and be mounted on the robotic hand to perceive the shear and normal force when grasping a cup. Dynamic piezo-tribo hybrid contact architecture serves for both low power consumption and high sensitivity. The annular hierarchical wrinkles and the hybrid self-powered architecture could realize surface texture recognition.